Peran Kepala Desa dalam Pengelolaan Badan Usaha Milik Desa di Desa Nyangkowek Kecamatan Cicurug Kabupaten Sukabumi - Enggi Dwi Riyani; Evi Priyanti; Hanny Purnamasari (Peneliti.net, 2022)
This study aims to identify and describe the role of the village head in managing village-owned enterprise policies on empowering the community of Nyangkowek Village, Cicurug District, Sukabumi Regency. In line with the title of the research, this research uses qualitative research using methods, interviews, documentation and observation. Based on the results of the study, it can be concluded that the village heads as a leader and decision maker as well as a motivator and facilitator is very important in determining success and success in all programs and activities in the village. Therefore, the function of the village head must be carried out properly for the implementation of village development and development. Therefore, a village head must be more active in communicating and taking direct action with the community in order to become an effective leader role for the village community.